Tracking proteasome degradation: A cross-organ analysis via intact degradomics mass spectrometry - Katharina I. Zittlau; Daniel Zachor-Movshovitz; Yegor Leushkin; Roy Schimmel Brener; David Morgenstern; Gili Ben-Nissan; Michal Sharon (Proceedings of the National Academy of Sciences, 2025)
The proteasome is a multisubunit degradation machinery that is essential for maintaining protein homeostasis by breaking down unnecessary or damaged proteins into peptides. While most of these peptides are further processed into amino acids, a subset evades complete degradation and plays key roles in biological processes such as antigen presentation, signaling, and apoptosis. However, the variability in peptide lengths and the diverse composition of proteasomes make their comprehensive identification and characterization particularly challenging. Here, we present a method that enables real-time identification of generated peptides, as well as uncleaved and partially cleaved protein substrates, revealing the processive nature of protein proteasomal degradation. Our intact degradomics workflow is based on intact mass spectrometry measurements and treats the enzymatically produced peptides as if they were generated within the mass spectrometer, akin to top–down products. We applied this approach to determine the kinetic profile of proteasome degradation and compare the real-time activity of proteasomes isolated from different mouse organs, uncovering distinct functionalities of the complex. Overall, this method offers a valuable tool for studying peptide degradation products across various proteasome configurations, while also enabling the investigation of how interacting proteins, inhibitors, and activators influence proteasome activity. Furthermore, its adaptability makes it applicable to a wide range of other proteolytic complexes, broadening its potential impact in the field.